DETERMINAN KREDIT MACET PADA BUMK DI KECAMATAN KUTAPANJANG KABUPATEN GAYO LUES - Riska Armaya -; Iqlima Azhar; Nasrul kahfi Lubis (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2022)
This study aims to determine the factors that affect bad loans at BUMK in Kutapanjang District, Gayo Lues Regency. The population of this research is the recipients of the BUMK savings and loan funds in the Kutapanjang sub-district. The sampling technique used purposive sampling method. Data collection was done by distributing questionnaires to 64 respondents. The data obtained were then analyzed using SPSS (Statistical Package for the Social Science). The research method used is a quantitative method. The results of this study indicate that business conditions have a positive and significant effect on BUMK bad loans, community income has a positive and significant effect on BUMK bad loans and community character has a positive and significant effect on BUMK bad loans in Kutapanjang District, Gayo Lues Regency. Based on the experience of researchers in this research process, there are several limitations in this study such as the number of research respondents who are not many so that they are still not sufficient to answer the actual situation and when collecting information and data through questionnaires there are some people who do not want to fill out the questionnaire. Then for further researchers it is recommended to add a few more variables such as the community's ability to manage the business, the firmness of the BUMK management